The Role of Students in Transition from School to College: Different Challenges in Elt - Jeyagowri, K.; Ilankumaran, M. (International Journal of Engineering and Technology, 2018)
This paper depicts the predicament of the transitional students who have shifted from school to college. The challenges of the students’ tenacity in learning English have been observed from the perspective of their transitional dilemma. The external and internal challenges of the students during the phase have also been discussed in this paper. It examines the changes of the adolescents’ attitude, emotions and stress. The paper also offers some strategies to come out of the crisis. In the globalization era, the classical method of teaching English that is teaching the language in the confined four walls have to be transformed into various activity based teachings which strengthen the teacher–student interaction in many ways. The subject English is helpful and effective in curriculum. The experts of textbooks have planned or designed itto prepare the learners use the language proficiently. The practice of English in secondary education is considered to be arising so many problems. The expected time frame for completion of the syllabus exceeds when the level of students are a combination of the vernacular medium and the English medium. This article unveils the factors which affects the process of English language learning among the students. A secondary level student who passed with merit or distinction cannot face the challenges after graduation. Those students struggle to write their own CV appropriately. Apart from that even the professionally trained teachers are unable to write the leave letter properly. Some of the important problems and complications of the rural students are also highlighted in the paper. Teaching in rustic and urban regions in India faces numerous issues in the academic framework like insufficient materials in government schools, lack of skilful teachers, lack of teaching quality, etc. This paper uncovers different complications in the system of education and recommend solution for them.
Keywords: Transition; transitional dilemma; classroom; curriculum; syllabus; adolescents; rural and urban students; secondary level.